An Epistemic Network Approach to Teacher Students’ Professional Vision in Tutoring Video Analysis - Farrell, Meg; Martin, Monika; Renkl, Alexander; Rieß, Werner; Könings, Karen D.; van Merriënboer, Jeroen J. G.; Seidel, Tina (Frontiers in Education, 2022)
Video-based training offers teacher students approximations of practice for developing professional vision (PV; i.e., noticing and reasoning) of core teaching practices. While much video analysis research focuses on whole-classroom scenarios, for early PV training, it is unclear whether the focused instructional context of tutoring could be an appropriate and potentially supportive design element. The present study describes 42 biology teacher students’ performance on a tutoring video analysis task. With qualitative content analysis, we investigated how teacher students describe and interpret noticed tutoring events, with particular reference to research-informed PV indicators. With epistemic network analyses, we explored co-occurrences of PV indicators across teacher students’ six video analysis responses, contrasting low and high quality description and interpretation network models, respectively. We found that teacher students’ skills paralleled previous PV literature findings on novices (e.g., vague, general pedagogy descriptions). Yet, unexpectedly, some teacher students demonstrated aspects of higher sophistication (e.g., describing individual students, making multiple knowledge-based interpretations). Findings suggest tutoring is a powerful context for showing tutor-student interactions, making it suitable for initial teacher students’ PV training. Moreover, results offer hints about the range of teacher students’ PV mental models and highlight the need for more support in content-specific noticing and reasoning. Nevertheless, tutoring representations within PV video analysis training may offer teacher students support in student-centered attention and knowledge-oriented focus.